Report of a group of Anglican and Free Churchmen who visited Spain, January 29 to February 9, 1937 - Underhill, Francis ; et al; Duncan-Jones, A. S. (Arthur Stuart), 1879-1955 (1937)
1937 018b-0070-004 292/946/18b/70(iv)